Buildability Attributes at Design Phase in Malaysian Building Construction - Hussein Mydin, Shaik; Mohamad Zin, Rosli; Abd Majid, Muhd Zaimi; Zahidi, Mardiyah; Memon, Aftab Hameed (International Journal of Sustainable Construction Engineering and Technology, 2011)
In Malaysian construction industry, problem is a common occurrence that hinders the project to run smoothly, notably in traditional contracting system where the design and construction process are separated. Previous research revealed that buildability is able to minimise these problems as it link the design and construction. This study outlines the buildability in design stage. Extensive reviews have been carried out on previous researches on buildability concepts, attributes, principles and other areas related to, and contributing to buildability mainly in the design phase. The term ‘buildability attribute’ has been selected in this study to describe those characteristics which directly or indirectly optimize integration of construction knowledge in the building process and balancing the various project and environment constraints to maximize project goals and building performance. Close examinations of available references revealed that altogether there are 19 buildability attributes that can be implemented during the design phase. The results of survey show that Malaysian construction industry practitioners rate the attribute Provide Clear and Complete Design Information (4.56) as the most important and Less Work Below Ground (3.60) as the least important attribute. The client, consultant and contractor share the same opinion regarding the most important and least important attributes, only higher instituiton’s view is slightly different. Out of 19 attributes, 11 attributes have mean values above 4.00, which indicate them as important attributes. This study has successfully measure the importance level of design buildability attributes for building construction in Malaysia.